Agile web development with Rails 7 - Ruby, Sam; Thomas, David 1956- (The Pragmatic Bookshelf, 2023)
Rails 7 completely redefines what it means to produce fantastic user experiences and provides a way to achieve all the benefits of single-page applications - at a fraction of the complexity. Rails 7 integrates the Hotwire frameworks of Stimulus and Turbo directly as the new defaults, together with that hot newness of import maps. The result is a toolkit so powerful that it allows a single individual to create modern applications upon which they can build a competitive business. The way it used to be. This book helps you produce high-quality, beautiful-looking web applications quickly - you concentrate on creating the application, and Rails takes care of the details. Rails 7 brings many improvements, and this edition is updated to cover the new features and changes in best practices.
Includes bibliographical references. - Description based on print version record
Keywords: Ruby on rails (Electronic resource); Web site development; Application software -- Development; Agile software development; Ruby (Computer program language); Object-oriented programming (Computer science); Sites Web; Développement; Logiciels d'application; Développement; Méthodes agiles (Développement de logiciels); Ruby (Langage de programmation); Programmation orientée objet (Informatique); Application software; Development